Teaching Challenges and Reflective Practices of Pre-service EFL Teachers during Teaching Practicum - Hustiana; Rafiqa; Nur Husnil Khatimah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigated the teaching practices, challenges, and reflective thinking of seven pre-service EFL teachers during their teaching practicum at SMPN 1 Majene, Sulawesi Barat. Employing a descriptive qualitative design, data were collected through structured classroom observations and post-teaching interviews. Data were analyzed using thematic analysis, in which observation notes and interview transcripts were systematically coded, categorized into recurring themes, and interpreted in relation to the study's research objectives. The findings reveal that while all participants demonstrated foundational instructional competencies including lesson review, ice-breaking activities, and student assessment considerable variation existed in lesson structure, media use, classroom communication, and student engagement. Classroom management emerged as the most prevalent challenge, with difficulties ranging from low voice projection and student passivity to poor time management and ineffective game implementation. Most participants attributed these challenges to personal factors, particularly insufficient preparation. Post-teaching reflections indicated meaningful self-awareness, as each teacher identified specific weaknesses and proposed contextually grounded improvements. Most notably, all seven participants unanimously selected gamification as their preferred instructional strategy for future teaching, signaling a shared recognition of the need for more interactive and engaging learning approaches. These findings suggest that pre-service EFL teacher education programs should strengthen training in classroom management, instructional variety, and gamification-based pedagogy to better equip novice teachers for authentic classroom demands.